2005
DOI: 10.1149/1.1954967
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Characterizations on Si and C-Coated Si Particle Electrodes for Lithium-Ion Batteries

Abstract: The understanding of cycling and electrochemical characteristics of Si particle anodes for Li-ion batteries has previously been hindered by very fast capacity fading. Optimizing the electrode architecture to significantly improve its stability up to the 1000mAh∕g charge-discharge level has made it possible to investigate these properties to a greater depth than before. The capacity fading and lithiation mechanisms of Si and C-coated Si particles have been studied in this paper by cycling test and electrochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(84 citation statements)
references
References 18 publications
7
77
0
Order By: Relevance
“…2b).The amount of carbon within the composite powder, as determined by the elemental analysis, was 29 wt.%. Previous Raman study has confirmed that the C coating produced under the present condition is partially (*50%) graphitic in nature [7]. Figure 3 compares the XRD patterns of the SiO powder before and after the C-coating process.…”
Section: Microstructural Characterizationsupporting
confidence: 66%
See 1 more Smart Citation
“…2b).The amount of carbon within the composite powder, as determined by the elemental analysis, was 29 wt.%. Previous Raman study has confirmed that the C coating produced under the present condition is partially (*50%) graphitic in nature [7]. Figure 3 compares the XRD patterns of the SiO powder before and after the C-coating process.…”
Section: Microstructural Characterizationsupporting
confidence: 66%
“…Among them, Si and Si-containing compounds are of great interest [1][2][3][4][5][6][7][8][9], owing to their large potential specific capacities, low cost and environment-benign nature. In spite of these advantages, all these anode materials suffer from serious volumetric expansion and contraction during charge/discharge (C/D) cycling.…”
Section: Introductionmentioning
confidence: 99%
“…͑Typi-cal C/D potential curves of the C-coated Si electrode can be found in Ref. 6.͒ The irreversible capacity of the first cycle is ϳ50 mAh/g, while it reduced to ϳ20 mAh/g after the fifth cycle. Accelerated fading, nevertheless, took place beyond the 50th cycle.…”
Section: Resultsmentioning
confidence: 99%
“…The plots can be satisfactorily simulated by an equivalent circuit consisting of an electrolyte resistance in series with a Randles-type impedance element and a blocking CPE as shown in the inset of Fig. 2c [30,31]. In the equivalent circuit, CPE1 is the constant phase element for the Si-C/electrolyte interface, R 1 is the charge transfer resistance at the Si-C/electrolyte interface, Z w is the generalized Warburg impedance, CPE2 is the constant phase element for the Si/C interface, R 2 is the electrolyte resistance at the Si/C interface, CPE3 is the constant phase element for the grain-boundary of Si powders, R 3 is the charge transfer resistance between Si grains.…”
Section: Resultsmentioning
confidence: 99%